2015
DOI: 10.1007/s13204-015-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly oriented and physical properties of sprayed anatase Sn-doped TiO2 thin films with an enhanced antibacterial activity

Abstract: Pristine TiO 2 and Sn-doped TiO 2 thin films with different Sn doping levels (2, 4, 6 and 8 at.%) were deposited by employing a simplified spray pyrolysis technique. The XRD pattern of the films confirmed tetragonal structure with the polycrystalline nature. The films exhibited a pure anatase titanium dioxide (TiO 2 ) with a strong orientation along (101) plane. The scanning electron microscopy image of 6 at.% Sn-doped TiO 2 thin film depicted nanosized grains with porous nature. The atomic force microscopy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Macrostrain can be defined by using the peak shift with the residual stress analysis, and microstrain can be obtained from the integral breadth . The lattice strain ( ε ) was calculated by using the following formula: ε=βcosθ4, …”
Section: Resultsmentioning
confidence: 99%
“…Macrostrain can be defined by using the peak shift with the residual stress analysis, and microstrain can be obtained from the integral breadth . The lattice strain ( ε ) was calculated by using the following formula: ε=βcosθ4, …”
Section: Resultsmentioning
confidence: 99%
“…The refractive indexes of photoanodes are shown in Figure 6. The reason of decrease in refractive index at higher wavelength and finally attaining a constant value may be the presence of high porosity in these films 58,59 …”
Section: Resultsmentioning
confidence: 99%
“…The lattice strain of the films is almost constant at ~2.9299 × 10 −3 (Table ). Dhanapandian et al have observed a slightly high strain of 3.3663 × 10 −3 in Sn‐doped TiO 2 thin films.…”
Section: Resultsmentioning
confidence: 99%
“…The dislocation density of the films increases with the Mo dopant concentrations from 7.1 × 10 15 to 1.0 × 10 20 lines/m (Table ), because of the difference in ionic radii of Ti and Mo ions. Similar results have been observed by Dhanapandian et al when Sn is doped into TiO 2 for antibacterial applications.…”
Section: Resultsmentioning
confidence: 99%